Hadis-Hadis Tentang Penyakit Hati dan Dampaknya Negatifnya Terhadap Kesehatan - S, Muhammad Arief; Adnir, Farid (Hikmah, 2023)
Negative reactions from those around a person struggling with mental health issues are common. This is due to widespread ignorance about mental health issues. Some people are unable to accept more scientific explanations of mental illness and opt out of medical and psychiatric treatment due to cultural and religious norms that attribute mental health problems to supernatural causes. With regard to the Hadiths on liver diseases, this study aims to analyze the variety of Hadiths that talk about liver diseases and their impact on one's health. The research method used is the Maudu'i method, which means that the author examines the traditions that correlate to the research topic. The results of the study explain that in the hadith the disease of the heart is called wahn, which is the fear of death, love of luxury, love of what is in the world with mere lust. The disease of the heart will result in riya', ujub, takabur, ghadab, ghibah, and hasad. Then the way to prevent the disease of the heart from dwelling in oneself is, prejudging well, getting closer to Allah, dhikr, eating from halal products because something halal will change a pure body, and finally fasting, because fasting can restrain lust.